New Tools for Studying Network Industry Reforms in Developing Countries: The Telecommunications and Electricity Regulation Database - Wallsten, Scott; Clarke, George; Haggarty, Luke; Kaneshiro, Rosario; Noll, Roger; Shirley, Mary; Colin Xu, Lixin (World Bank, Washington, D.C., 2013)
Infrastructure industries-including telecommunications, electricity, water, and gas-underwent massive structural changes in the 1990s. During that decade, hundreds of privatization transactions valued at billions of dollars were completed in these sectors in developing and transition economies. While privatization has received the most attention, reforms also included market liberalization, structural changes like unbundling, and the introduction of new laws and regulations. To date, regulations have received far less attention than their potential economic effects warrant, largely due to lack of data. In order to address this problem, the authors set out to compile a comprehensive and consistent dataset through an extensive survey of telecommunications and electricity regulators in developing countries. The authors describe the surveys and the resulting database. The database of telecommunications regulations includes 178 variables on regulatory governance and content in 45 countries. The database of electricity regulations includes 374 variables in 20 countries.